The impact of the enquiries and the special legislation on the state of education in the Italian Mezzogiorno (1861-1914) - Brunella Serpe (Ricerche di Pedagogia e Didattica, 2025)
This essay reflects on the grave problems affecting education in the Italian continental and insular Mezzogiorno from the proclamation of national unity to the Giolittian era. Despite the new measures introduced by the Coppino law of 1877, which among other things included obligatory schooling, no significant transformations of the Mezzogiorno were seen for many decades. This is demonstrated by the “special laws” of 1904 and 1906, respectively aimed at Basilicata and Calabria, which sought to tackle general and specific problems by means of extraordinary funding not just for schools but also agricultural and professional training, still inadequate in those regions. Together with the studies, enquiries and statistical surveys that were conducted, in addition to the documentation available in the archives, these laws and other extraordinary measures constitute materials with which to explore and reflect on the theme of this essay. This encompasses illiteracy and the steps taken in response to it, the lack of school buildings, the grave social problems and the role of educational policies in the various areas of the Italian Mezzogiorno.